3D finite element modeling of in-service sleeve repair welding of gas pipelines. (October 2016) - Alian, Ahmed R.; Shazly, Mostafa; Megahed, Mohammad M.
Abstract: The present work investigates the influence of welding sequence and scheme on residual stresses induced during in-service sleeve repair welding of gas pipelines. For this purpose, a 3D thermo-mechanical FE analysis is conducted on an 8″-Schedule-20, API 5L-X65 steel pipe. Two welding sequences for the sleeve-pipe circumferential fillet welds are compared in the present study: sequential welding in which one side of the sleeve is welded first and then the other side is welded by the same welder, and simultaneous welding in which both sides of the sleeve are welded concurrently by two welders. Within the simultaneous welding sequence, four different welding schemes, designed to investigate the influence of the number of welders and welding directions on residual stresses, are investigated. The results show that the sequential welding sequence induces less residual stresses and distortions. Within the simultaneous welding sequence, the back-step welding scheme is found to induce the least average residual stresses as compared to other welding schemes. Highlights: We model in-service sleeve repair welding using 3D FE. Model was validated through comparison with existing experimental results. The study presents results on the effect of both welding sequence and welding scheme on the resulting residual stresses. Sequential welding sequence generates lower residual stresses than simultaneous welding sequence. Back-step welding scheme generates the lowest average residual stresses along the pipe circumference.